Metastatic Alveolar Soft Part Sarcoma Responsive to Pazopanib after Progression through Sunitinib and Bevacizumab: Two Cases - Read, William L. (Case Rep Oncol, 2016)
Alveolar soft part sarcoma (ASPS) is a rare soft tissue sarcoma with a propensity for lung metastases and indolent progression. ASPS is not responsive to chemotherapy, but there are case reports and small series describing benefit from drugs targeting the VEGF pathway. These drugs include sunitinib, cediranib and bevacizumab. There is no established second-line treatment for persons with ASPS progressing through first-line targeted therapy. We report two individuals with metastatic ASPS who obtained disease stabilization from sunitinib lasting over a year. After subsequent progression through sunitinib and second-line bevacizumab, both individuals again had disease response and subsequent stabilization from pazopanib.